المواطنة في الفقه الإسلامي بين المؤيدين والمعارضين : دراسة تحليلية لوضع غير المسلمين في نظام الحكم الإسلامي /cإعداد، معاد بن أحمد - أحمد، معاد (Kulliyyat Ma'arif al-Wahy wa al-'Ulum al-Insaniyah, International Islamic University Malaysia, 2010)
The question on the status of non-Muslim residents in an Islamic state is one of the issues that is currently been debated extensively. This is especially so when the issue is tied down to the attempt to create an Islamic state, because the modern nation states including Muslim countries have already adopted the citizenship system, and this system has become the only way to legally categorize the citizen and non-citizen regardless of religious affiliation, and original background of the person. The history of Islam has shown that such system has never been practiced or perceived since the time of Prophet Mohammad (s.a.w) until the collapse of Ottoman Caliphate in 1924. Therefore, this thesis will embark on philosophical foundation of the concept of citizenship: its definition, origin and usage. Also, most importantly, the question whether such conception is in line with the Dhimmah system will be investigated. The views of different Islamic scholars on the status of non-Muslims in an Islamic state will be analyzed. In addition, the evidences from Qur'an, Sunnah and 'Aql (intellect) will be presented. Then, policy recommendation on the status of non-Muslim citizens and their various rights in the Islamic state will be provided based on the strongest evidences and Shari'ah principles. The methodologies employed in this thesis are comparative description and analysis.